2016
DOI: 10.1016/j.anr.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Peer Attachment, Perceived Parenting Style, Self-concept, and School Adjustments in Adolescents with Chronic Illness

Abstract: Healthcare providers can promote the process of school adjustment in several ways, such as discussing this issue directly with adolescent patients, along with their parents and peers, examining how the organization and content of the treatment can be modified according to the adolescents' school life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
1
15
1
1
Order By: Relevance
“…Consistent with this study, results from a study by Rassart et al [ 19 ] indicated that perceptions of parental acceptance were positively correlated with CHD adolescent self-esteem. Warm and accepting parent-adolescent relationships contributed to the well-being of children and adolescents at risk [ 20 ], and were related to higher levels of QOL and fewer psychological symptoms in adolescents with chronic diseases [ 21 ]. Also, The QOL of adolescents suffering from inflammatory bowel disease positively correlated with the warm parental style [ 22 ] while the QOL of adolescents with diabetes type 1 was positively associated with mindful parental style [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this study, results from a study by Rassart et al [ 19 ] indicated that perceptions of parental acceptance were positively correlated with CHD adolescent self-esteem. Warm and accepting parent-adolescent relationships contributed to the well-being of children and adolescents at risk [ 20 ], and were related to higher levels of QOL and fewer psychological symptoms in adolescents with chronic diseases [ 21 ]. Also, The QOL of adolescents suffering from inflammatory bowel disease positively correlated with the warm parental style [ 22 ] while the QOL of adolescents with diabetes type 1 was positively associated with mindful parental style [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In numerous studies it has been found that the most negative style, due to its effects on children, is the negligent one, followed by the authoritarian one. The most functional have been, in this order, the indulgent and the authoritative [32,37,[43][44][45]. This research has not formulated this hypothesis related to authoritative or negligent styles because it was not among the objectives of this research to analyse these effects.…”
Section: Introductionmentioning
confidence: 98%
“…For example, monitoring (active parental supervision) was initially ambiguously conceptualized as a parenting practice that involves active attempts by the parents to watch over their children. However, several researchers have pointed out that, although parental monitoring is clearly related to a wide range of indicator variables of psychosocial adjustment, most of this positive relationship with the adjustment criteria corresponded to the importance of spontaneously revealing information to the parents (typical of the authoritative style), but not to the parents' intrusive attempts to extract information (typical of the authoritarian style) (Ahn & Lee, 2016;Calafat et al, 2014;Carroll et al, 2016;Holdsworth, Laverty & Robinson, 2017;McLaughlin, Campbell & McColgan, 2016;.…”
Section: Introductionmentioning
confidence: 99%